Generation Z; using the AIDA model to evaluate marketing activities implications on the student application process for vocational schools; case study in Kosovo - Art Shala (Technium Social Sciences Journal, 2020)
Generation Z content consumption, sharing of information and decision-making process is continuously being studied by practitioners and academia; as it is still considered in its formation. This study sheds light on the decision-making process followed by applicants that have become part of a technical vocational school in Kosovo. This study uses the AIDA model to evaluate the process for Attention development, interest creation, desire formation and action taking. 115 respondents have been part of the study. The findings from the study showcase that word-of-mouth across friends and family are of pivotal importance to respondents for awareness generation activities. Following this, the applicants have undertaken further discussions with other friends and relatives, navigated the social media pages and the website of the school to best get informed prior to taking a decision to submit their application to the school.